ANALYSIS OF THE COST OF THE DISEASE - PROBLEMS AND SOLUTIONS - V.V. Omel'yanovskii; M.V. Avksent'eva; E.V. Derkach; N.D. Sveshnikova (Union of pediatricians of Russia, 2011)
The article discusses the estimation of the disease value, which includes direct, indirect and «intangible» costs. Advantages and disadvantages of different approaches to cost accounting, including the method of direct costs microcalculation compared with established norms of reimbursement are presented. It is demonstrated that disease's cost not only reveals the burden of a pathology, but also allows the State to rationally allocate resources. The authors conclude that lack of comparability of the results of studies with different approaches to cost accounting does not allow their use in health care management. To solve this problem is necessary to develop a common methodology for analyzing the cost of the disease.Key words: cost of illness study, clinical and economical analysis, direct cost, indirect cost, impalpable costs, microcalculation of costs, human capital method, friction costs method, absenteeism, presenteeism.